THE EFFECT OF KEY AUDIT MATTERS, AUDIT COMMITTEE MEETING FREQUENCY AND PRIOR YEAR AUDIT OPINION ON AUDIT DELAY - Irna Danita; Hardi; Meilda Wiguna (Universitas Riau, 2026)
The purpose of this study is to look into how audit delays in Indonesian public companies for the years 2022–2024 are affected by the frequency of audit committee meetings, key audit concerns (KAM), and the audit opinion from the previous year. The conflicting results of previous studies on the causes of audit delays and the continuation of financial report release delays in Indonesia despite strict regulations established by the Financial Services Authority (OJK) served as the impetus for this study. The recently passed ISA 701 on KAM disclosure in 2022 is also highlighted in this research. The research team employed Multiple Linear Regression (MLR) and SPSS to examine the data. Purposive sampling was used to pick the sample, which consisted of public corporations that had audit delays during the observation period. Data sources included annual reports and audited financial statements that were posted on the Indonesia Stock Exchange. The frequency of audit committee meetings was shown to be unaffected by KAM, the audit opinion from the prior year had a large negative influence, and KAM had a positive and significant impact on audit delay.